Dogan, M.: Elite Configurations at the Apex of Power: In Lumumba-Kasongo, T.–Patterson, R.– Sasaki, M. eds.: International Studies in Sociology and Social Anthropology. Vol. LXXV, Leiden-London: Brill, 2003. (Szociológiai Szemle, 2024)
-